Key Technologies of Automatic Test System for Train-control Vehicle-borne Software - HE Xiezhen; WANG Yeliu; ZHOU Zhifei (机车电传动)
In order to realize the automated validation testing of the train-control vehicle-borne software, a novel kind of implement mechanism for the train-control vehicle-borne software automatic test system was proposed. The key technologies of automatic test systemmodel-driven hardware-in-loop simulation technology and test script technology were introduced in detail. These technologies had been successfully applied in the LKJ, as well as a new generation of train-control vehicle-borne equipment automatic test system, which had greatly improved the efficiency and quality of the testing.